Nanofluid as a coolant for electronic devices (cooling of electronic devices) - Ijam, A.; Saidur, Rahman (Applied Thermal Engineering, 2012)
Nanofluids are the suspension of ultrafine solid nanoparticles in a base fluid. Nanofluids are expected to be a promising coolant candidate for thermal management system of next generation high heat dissipation electronic systems. Nanofluids are used with different volume fractions. A minichannel heat sink with a 20 x 20 cm bottom is analyzed for SiC-water nanofluid and TiO(2)-water nanofluid turbulent flow as coolants through hydraulic diameters. The results showed that enhancement in thermal conductivity by dispersed SiC in water at 4 volume fraction was 12.44 and by dispersed TiO(2) in water was 9.99 for the same volume fraction. It was found that by using SiC-water nanofluid as a coolant instead of water, an improvement of approximately 7.25-12.43 could be achieved and by using TiO(2)-water 7.63-12.77. The maximum pumping power by using SiC-water nanofluid at 2 m/s and 4 vol. was 0.28 W and at 6 m/S and 4 volume equal to 5.39 W. By using TiO(2)-water nanofluid at 2 m/s and 4 vol. it was found to be 0.29 W and 5.64 W at 6 m/s with the same volume of 4.